Foreign Direct Investment in the Pharmaceutical Industry: Why Singapore and not Hong Kong. Issue 2 (17th November 2015) - MERCURIO, Bryan; KIM, Daria
Abstract: This article began as mere curiosity over what appeared to be a paradox – Singapore and Hong Kong share countless economic and geopolitical similarities and compete vigorously for foreign direct investment (FDI), yet only the former has become a pharmaceutical hub while the latter struggles to attract any FDI in the sector. To find the reason for the "drastic" difference in pharmaceutical FDI, we compare the economic, legal, policy, and regulatory frameworks of the two jurisdictions focusing on the factors that have been identified in the economic literature as having the most relevance for FDI decision-making. The analysis discounts economic and legal factors before finding variances in policy and regulatory frameworks as the critical difference accounting for the disparity in the pharmaceutical FDI. Given that Hong Kong occasionally considers transforming itself into the "pharmaceutical centre for the Asia-Pacific", this article calls for a change in policy approach and strategy before this aspiration is considered more realistically.